The Effectiveness of Al2SO4, CaO and Crude Tannin Extract Originated From Averrhoa bilimbi Wood to Improve the Quality of Peat Water - Edi Perlindungan Silalahi; Budijono '; Sampe Harahap (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Peat water is categorized as low quality water as it has high organic matter, low pH, high TDS and turbidity and brownish colored. Crude tannin extract has been used for improving the peat water, but there is no information on the use of Averrhoa bilimbi tannin extract in improving the quality of the water. To understand effectiveness of the A. bilimbi tannin in improving the peat water quality, a study has been conducted in May – October 2015. There was a CRD method applied, with 4 treatments, P0 (control, without tannin extract), P1(10 mlL-1), P2(20 mlL-1) and P3(30 mlL-1). In each treatment unit, 8 liters peat water was added with Al2SO4 (2 grL-1) and CaO (2.7 grL-1) and then was added with various dosages of tannin extract. The treated water was kept for 3 hours and the water quality parameters were measured. The treated water was then used to rear Cyprinus carpio. Results shown that the treated water quality was improved, there was degradation in organic matter content, turbidity and colour, while pH, DO and TDS was increase. The best treatment was obtained in P1, as the organic matter decrease, from 1,145.5 to 151.97 mg/L, the turbidity decrease, from 1,005.66 to 26 NTU and color also decrease, from 29,000.33 to 389 PtCo. The highest survival rate of C. carpio after being reared for 4 days was also found in the P1 treated water, that was 97%. Based on the data obtained, it can be concluded that the crude tannins extracts from A. bilimbi wood is effective to improve the quality of peat water.Keywords : Peat Water, tannins, Cyprinus carpio, Averrhoa bilimbi